Analisis Profitabilitas Usahatani Tembakau Petani Mitra Pt. Djarum Kecamatan Bulu Kabupaten Temanggung - N.A.W. Putri; A. Setiadi; S.I Santoso (Agroland: Jurnal Ilmu-ilmu Pertanian, 2018)
ABSTRACT The purposes of this research were to analyze the income of tobacco partner farmers and to analyze the profitability of the tobacco farming system in Bulu sub district, Temanggung district. The research was conducted on 21th December 2017 to 21th January 2018. The research used a census method with which sampling of 78 partner farmers of tobacco was selected. Data was analyzed using income analysis, profitability analysis and One Sample t-Test. The result showed that the average of the income from the tobacco partner farmers was IDR 8,966,784.00 each month with 271.33 % profitability. The results showed that the income from the tobacco farmers partner is greater than the minimum wage in Temanggung district and  the tobacco farm is profitable and recommendable for getting credit because its profitability value is greater than that the deposits interest rate and the credit interest rate of BRI Bank. Key words : farming, income, partnership, profitability, tobacco.